Diffuse-Type Caroli Disease with Characteristic Central Dot Sign Complicated by Multiple Intrahepatic and Common Bile Duct Stones - Moon Joo Hwang; Tae Nyeun Kim (Korean Society of Gastrointestinal Endoscopy, 2017)
Caroli disease (CD) is a rare congenital malformation of the liver characterized by non-obstructive, segmental, cystic dilatation of the intrahepatic bile ducts (IHDs). The clinical course is usually asymptomatic for the first 5-20 years, and symptoms may seldom occur throughout the patient's life. Bile stagnation leads to recurrent episodes of cholangitis, stone formation, or liver abscesses, and biliary cirrhosis usually occurs years later. Here we report on a 42-year-old man diagnosed with diffuse-type CD with a characteristic central dot sign, who had multiple intrahepatic and common bile duct (CBD) stones. CBD stones were treated successfully with endoscopic retrograde cholangiopancreatography (ERCP).